Aplikasi Sistem Penunjang Keputusan Pemilihan Obat Bagi Penderita Gagal Jantung - Trisnawarman, Dedi; Hartanto, Ferdinand (JIK: Jurnal Ilmu Komputer, 2007)
The purpose of this DSS program is to help doctor to make a decision. Sometimes, doctor is confuse with what medicine should be gave to the patient. This application can show some information, such as the treatment for heart disease. Also article that tell about what is heart failure, etc. One of the model is Analytical Hierarchy Process or AHP. AHP is use to give a value for the criteria. Some form that perform here are form home, form information, form article, form dss, form admin and form help. This DSS application uses Macromedia Dreamweaver MX 2004 for interface design, PHP as programming language, Apache as webserver, and MySQL as database and database server. Keywords: Decision Support System, AHP, Heart Failure